THE INFLUENCE OF KNOWLEDGE, ATTITUDE AND MOTIVATION OF HOUSEHOLD BEHAVIOR AND SPORT BEHAVIOR - Nur Chabibah; Rini Kristiyanti; Milatun Khanifah; Anis Sofiana (Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama, 2021)
Indonesia produces one million tons of garbage per day. The impact on health is to become a breeding ground for organisms that cause disease, poison animals and plants that are consumed by humans. Therefore, high public awareness is needed in the joint responsibility in waste management. This responsibility will be formed if each individual has the knowledge, attitude and motivation in waste management. The research aims to determine the effect of knowledge, attitudes and motivation on sorting and processing waste. The study was observational analytic with cross-sectional approach, which analyzed factors of knowledge, attitudes and motivations that influenced the behavior of household organic waste sorting and processing. The population in this study were all family heads in 05 residents of Podo Village, Kedungwuni District, Pekalongan Regency. The sampling technique uses cluster random sampling, with a large sample of 57 households. Data collection using questionnaires with interview techniques. Analysis of the data in this study using chi square with the level of significance used in this test was p-value <0.05 on 95% confidence interventions. The results of statistical analysis there is the influence of knowledge on the behavior of household heads in conducting the behavior of waste sorting, (p-value = -0.048; CI -0.228 s.d -0.449). The influence of attitudes and on the behavior of family heads in conducting the behavior of waste sorting (p-value = 0.002; CI -0.423 to 0.076). Influence of motivation and on the behavior of household heads in conducting waste sorting behavior (p-value = 0.027; CI-0313 s.d 0.050). But there is no influence of knowledge on the behavior of family heads in conducting the behavior of waste management, (p-value = 0.174; CI-0.006 to 0.174). The influence of attitudes on the behavior of family heads in conducting the behavior of waste management, (p-value = 0.034; CI-0.007 to 0.257). The influence of motivation on the behavior of the head of the family in conducting the behavior of garbage processing, (p-value = 0.034; CI -0.257 to 0.007). It was concluded that there is an influence of knowledge, attitude and motivation about sorting and processing of rubbish on the behavior of sorting and processing of household waste.